Development of an intranasal vaccine for SARS-CoV-2 - Roberts, Scot (Henry Stewart Talks, 2020)
General mechanism of action of DNA vaccines, Adenoviral vectors for DNA delivery to host cells -Advantages and limitations of intranasal vaccines, Cellular, mucosal and antibody immunity in the context of SARS-2, Stability of AdCOVID at room temperature, Earliest possible approval of AdCOVID, How far and how fast can this vaccine then be deployed?